Environmental indicators in effluent assessment of rainbow trout (Oncorhynchus mykiss) reared in raceway system through phosphorus and nitrogen - M. A. B. Moraes; C. F. Carmo; Y. A. Tabata; A. M. Vaz-dos-Santos; C. T. J. Mercante (Brazilian Journal of Biology)
Abstract The phosphorus and nitrogen discharge via effluent of intensive trout farming system was quantified through the use of environmental indicators. The nutrient loads, the mass balance, the estimated amount of nutrients in feed and the amount of nutrients converted in fish biomass were calculated based on the concentrations of phosphorus (P) and nitrogen (N) in the feed and in the water. Of the offered feed, 24.75 kg were available as P and 99.00 kg as N, of these, 9.32 kg P (38%) and 29.12 kg N (25%) were converted into fish biomass and 15.43 kg P (62%) and 69.88 kg N (75%) were exported via effluent. The loads and the mass balance show the excessive discharge of nutrients via effluent, corroborated by the feed conversion ratio (2.12:1) due to the low efficiency of feed utilization, therefore, it is proposed the use of this zootechnical parameter as environmental indicator. In addition, feed management practices are not adequate, highlighting the low frequency of feeding during the day, excessive amount and low quality of feed offered. These results demonstrate the need for adequate feed management and the need for careful monitoring of effluent.